DAMPAK KETIDAKSESUAIAN AKAD IJARAH TERHADAP KEPERCAYAAN NASABAH DI BANK SYARIAH - RWulandari, Septiayu; Yudianto, Ahmad (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2022)
Abstract The study explores the impact of non-compliance with the Ijarah contract on customer trust in Islamic banks. The Ijarah contract, a lease agreement in Islamic finance, must adhere strictly to Sharia principles. Any deviation can undermine customer trust, leading to potential reputational and financial losses for the banks. This research examines the factors contributing to such discrepancies, including regulatory challenges, operational issues, and lack of staff training. The findings suggest that enhancing transparency, ensuring strict compliance with Sharia guidelines, and improving customer communication are crucial for maintaining customer trust. The study underscores the importance of regulatory harmonization and continuous staff education to uphold the integrity of Islamic banking operations. Keywords: Ijarah, Islamic Banking, Customer Trust, Sharia Compliance, Regulatory Challenges